Analysis of the possibility of non-destructive testing to detect defects in multi-layered composites reinforced fibers by optical IR thermography. (1st April 2019) - Pracht, Monika; Swiderski, Waldemar
Abstract: The paper analyses the possibilities and effectiveness of using infrared thermography with optical thermal excitation by reflection approach in the case of multilayer composites reinforced fibers. The advantages and limitations of this technique have been demonstrated via composites reinforced with three types of fibers: glass, aramid, and carbon. The most common defects in such structures are: delaminations, fiber cracks, matrix cracks, and separation of fibers from the matrix. The paper describes some results of the numerical simulations of defects detection using optical IR thermography with the emphasis made on the inspection of multi-layer composite materials. The simulations were conducted in order to determine the detection of defects depending on the depth of their location under the front surface of composite material as well as their geometrical dimensions.